Initial pull-out strength of tendon sutures: An in vitro study in sheep Achilles tendon - (:unkn) unknown (AOFAS - American Orthopaedic Foot and Ankle Society, 2002)
Forty-eight fresh frozen sheep achilles tendons were used to compare the pull-out strengths of Kessler, Bunnell and locking loop techniques which are the standard configurations described for Achilles tendon repair. A simulated Achilles tendon rupture was done with a tenotomy made 2 cm proximal to the calcaneal insertion. One of the configurations was placed at the distal end of the proximal portion of the tendon specimens using No. 5 Ticron. The distal ends of the suture materials were left free and were not used to connect the proximal and distal portions of the tendon. Using a servohydraulic materials testing machine, each tendon was tested to failure in tension at a displacement rate of 20 mm/min. All the specimens failed due to pull-out of the suture material. Since the cause of failure was suture material breakage in the previous studies reporting repair strength, they were unable to represent the effect of configuration on the strength. This study is the first to represent the effect of configuration on the initial strength since there is no failure due to suture material breakage.
Keywords: Achilles tendon; In Vitro; Repair strength